The Determinants of Value-Added of Non-Oil and Gas Manufacturing Industries in Indonesia: Study case of 24 subsectors of non-oil and gas manufacturing industries from 2008 to 2019 - Detylia; Santoso, Dwi Budi (Journal of Indonesian Applied Economics, 2024)
This research aims to obtain the determinants of industrial value added in Indonesia from 2008 to 2019 and give suggestions to the government about the determinants of industrial value added in Indonesia so they can have relevant information to stipulate a regulation to improve the industrial value added in Indonesia. The scope of this research is restricted to twenty-four (24) subsector of the medium and large non-oil and gas manufacturing industry in Indonesia from 2008 to 2019 and are analyzed with Panel Data Analysis using Random Effects Estimators followed by specification test to make sure the credibility of the regression model (Pesaran CD Test, Hausman Test, Breusch-Pagan test). This panel data was collected from Central Statistics Indonesia Board from 2008 to 2019. Based on the GLS regression results, we found that the variable cost, labor cost, capital-intensive industries, and the implementation of the Law Number 3 of 2014 concerning Industry significant and positive impact on the value-added of non-oil and gas manufacturing industry, while fixed costs do not significantly affect the value-added. These findings align with the income theory that the profit is obtained by subtracting the total revenue from the production cost (variable cost, labor cost), except for fixed cost. By finding that the fixed cost does not significantly impact the value-added in the non-oil and gas manufacturing industry, it is suggested to deepen the research by using firm-level data instead of aggregate data and includes other variables that have significance to the value added. The research gap of this research is the harness of variable cost, fixed cost, and labor cost, which represent costs in the production theory, dummy variables of capital-intensive industries as a measure of the impact of capital-intensive to value-added, and dummy variables before and after the implementation of the industry law to measure the impact of the government’s role. As implications, it is suggested that the producers could optimize their economies of scale since the increased variable cost and labor cost positively impact the value added. Other suggestions, it is recommended that the government simplify the bureaucracy of the business process, incentivize the technology start-ups, and embed the Industry 4.0 infrastructure in the 24 subsectors of industries.